Correlated time variability of multicomponent high-velocity outflows in J162122.54+075808.4. Issue 4 (7th May 2021) - Aromal, P; Srianand, R; Petitjean, P
ABSTRACT: We present a detailed analysis of time variability of two distinct C iv broad absorption line (BAL) components seen in the spectrum of J162122.54+075808.4 ( z em = 2.1394) using observations from SDSS, NTT, and SALT taken at seven different epochs spanning about 15 yr. The blue-BAL component (with an ejection velocity, v_e37 500 km s −1 ) is an emerging absorption that shows equivalent width variations and kinematic shifts consistent with acceleration. The red-BAL component (v_e 15 400 km s −1 ) is a three-component absorption. One of the components is emerging and subsequently disappearing. The two other components show kinematic shifts consistent with acceleration coupled with equivalent width variability. Interestingly, we find the kinematic shifts and equivalent width variability of the blue- and red-BAL components to be correlated. While the C iv emission-line flux varies by more than 17 per cent during our monitoring period, the available light curves (covering rest frame 1300–2300 Å) do not show more than a 0.1 mag variability in the continuum. This suggests that the variations in the ionizing flux are larger than that of the near-ultraviolet flux. However, the correlated variability seen between different BAL components cannot be explained solely by photoionization models without structural changes. In the framework of disc wind models, any changes in the radial profiles of density and/or velocity triggered either by disc instabilities or by changes in the ionizing radiation can explain our observations. High-resolution spectroscopic monitoring of J1621+0758 is important to understand the physical conditions of the absorbing gas and thereby to constrain the parameters of disc wind models.